Global Health Governance and Global Power: A Critical Commentary on the Lancet-University of Oslo Commission Report. (April 2016) - Gill, Stephen; Benatar, Solomon
The Lancet–University of Oslo Commission Report on Global Governance for Health provides an insightful analysis of the global health inequalities that result from transnational activities consequent on what the authors call contemporary "global social norms." Our critique is that the analysis and suggested reforms to prevailing institutions and practices are confined within the perspective of the dominant—although unsustainable and inequitable—market-oriented, neoliberal development model of global capitalism. Consequently, the report both elides critical discussion of many key forms of material and political power under conditions of neoliberal development and governance that shape the nature and priorities of the global governance for health, and fails to point to the extent of changes required to sustainably improve global health. We propose that an alternative concept of progress—one grounded in history, political economy, and ecologically responsible health ethics—is sorely needed to better address challenges of global health governance in the new millennium. This might be premised on global solidarity and the "development of sustainability." We argue that the prevailing market civilization model that lies at the heart of global capitalism is being, and will further need to be, contested to avoid contradictions and dislocations associated with the commodification and privatization of health.